Key Elements of Successful Management of Nglangeran Cocoa Agrotourism in Gunung Kidul Regency and Senare Regency, Indonesia - I Wayan Sweca Yasa (Yayasan Siti Widhatul Faeha, 2025)
Agritourism management refers to organizing agricultural activities to attract tourism, offering visitors direct experiences with farming life. It has gained importance as a strategy to increase farmers' income, support rural development, and preserve cultural traditions. This study explores the key factors behind successful cocoa agritourism management in Indonesia, focusing on Kampung Coklat Senare (KCS) and Griya Coklat Nglangeran. A qualitative descriptive approach was used, with data gathered from both primary (observations, interviews, documentation) and secondary sources (literature reviews and credible online publications). Fieldwork was conducted in Nglangeran Village (Yogyakarta) and Senare Village (North Lombok, NTB). Findings highlight institutional strength as a crucial factor in Nglangeran's agrotourism success. In contrast, Senare lacks sufficient institutional support, with minimal local government involvement, weak promotion, limited innovation in human resources, and poor integration with nearby attractions. Both sites allow tourists to engage in cocoa processing activities. Nglangeran applies a community-driven and conservation-focused tourism model, while Senare adopts an educational approach. Despite differences, both have embraced sustainable agriculture-based tourism, contributing to local economic growth and environmental conservation.